2009
DOI: 10.1186/1742-7622-6-5
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy dilution in randomized placebo-controlled vaginal microbicide trials

Abstract: Background: To date different vaginal gel microbicides have been evaluated in phase 2b/3 trials, but none have demonstrated effectiveness for preventing HIV infection. Failure to demonstrate effectiveness however does not necessarily indicate that a product is truly inefficacious, as several sources of efficacy dilution may compromise our ability to identify products that may have been truly efficacious.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
51
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 19 publications
(28 reference statements)
0
51
0
Order By: Relevance
“…Indeed, in the phase 3 Carraguard trial, where women were interviewed faceto-face, between 1 and 2% of women reported anal sex [12], similar to the percentage reporting anal sex among the FTFI group here, but considerably less than the 5-8% reported by ACASI participants. If unprotected anal sex is common and a large proportion of HIV infections are due to receptive anal intercourse, the ability to detect a protective effect in a vaginal product will be undermined [31].…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, in the phase 3 Carraguard trial, where women were interviewed faceto-face, between 1 and 2% of women reported anal sex [12], similar to the percentage reporting anal sex among the FTFI group here, but considerably less than the 5-8% reported by ACASI participants. If unprotected anal sex is common and a large proportion of HIV infections are due to receptive anal intercourse, the ability to detect a protective effect in a vaginal product will be undermined [31].…”
Section: Resultsmentioning
confidence: 99%
“…During clinical trials of intravaginal products, even modest rates of anal sex in a population may allow for HIV transmission and, if not accounted for, may mask the true effectiveness of a product. 11,12 Furthermore, anal sex was associated with lower reported rates of condom use, highlighting the importance of this sexual behavior even among heterosexual women. Current plans for clinical development of rectal microbicides include trials in women.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9] And high rates of unprotected anal intercourse may diminish the measured effectiveness of intravaginal products in preventing HIV infection. [10][11][12] In preparation for future studies of intravaginal HIV prevention methods, we assessed HIV risk behavior, HIV incidence, prevalence of STIs and vaginitis, vaginal practices, and retention in a newly described cohort of HIV-uninfected female sex workers (FSW) in urban Kenya. HIV prevalence from 30% to 67% has been documented in Kenyan FSW cohorts, 13,14 however recent attempts to identify HIVuninfected FSW cohorts with incidence sufficient for HIV prevention trials have been difficult.…”
mentioning
confidence: 99%
“…However, the role of UAI as a determinant of heterosexual HIV epidemics has not been sufficiently examined [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%